2021
DOI: 10.1007/s00330-021-07938-2
|View full text |Cite
|
Sign up to set email alerts
|

Visual lung damage CT score at hospital admission of COVID-19 patients and 30-day mortality

Abstract: Objectives Chest CT has been widely used to screen and to evaluate the severity of COVID-19 disease in the early stages of infection without severe acute respiratory syndrome, but no prospective data are available to study the relationship between extent of lung damage and short-term mortality. The objective was to evaluate association between standardized simple visual lung damage CT score (vldCTs) at admission, which does not require any software, and 30-day mortality. Methods In a single-center prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 23 publications
0
16
0
3
Order By: Relevance
“…Of note, a CT lung score of 15/24, which roughly translates a lung lesion burden (LLB) of 60% ( 8), was associated with a higher mortality rate, a rationale for a similar approach in COVID-19. It is intuitive to imagine the reversed linear correlation between lung lesion burden and the prognosis of COVID-19, there are some data supporting this correlation (10)(11)(12)(13)(14)(15); however, the available data regarding the dynamic changes of the CT during the disease's natural course are still limited in the current study (16).…”
Section: ' Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Of note, a CT lung score of 15/24, which roughly translates a lung lesion burden (LLB) of 60% ( 8), was associated with a higher mortality rate, a rationale for a similar approach in COVID-19. It is intuitive to imagine the reversed linear correlation between lung lesion burden and the prognosis of COVID-19, there are some data supporting this correlation (10)(11)(12)(13)(14)(15); however, the available data regarding the dynamic changes of the CT during the disease's natural course are still limited in the current study (16).…”
Section: ' Introductionmentioning
confidence: 77%
“…Many investigators have shown the potential association between initial CT findings, primarily the extent of pulmonary involvement, and adverse outcomes in patients with COVID-19 pneumonia (10,11,13,15,(25)(26)(27)(28)(29). Clinical endpoints and magnitude of the association with CT findings varied greatly between these studies, as did the extent of involvement used as the cut-off point.…”
Section: ' Discussionmentioning
confidence: 99%
“…COVID-19 pneumonia has an extremely variable prognosis [ 17 – 21 ]. While 80% of patients are either asymptomatic or have mild symptoms, 20% develop severe or profound disease and eventually die [ 22 25 ]. CT imaging of the lungs plays an important role in the care of patients infected with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), with the prognostic value of CT evaluated in several studies [ 9 14 , 18 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these studies are from China, Europe, and the United States, with no information available for patient cohorts in Japan [ 22 26 ]. In addition, several researchers have used image analysis software to quantify CT findings, making these impractical in daily clinical practice [ 25 27 ]. Practicality in clinical practice was our motivation to develop and evaluate the prognostic value of our visually-based assessment of CT lung findings (peripheral, multifocal, and diffuse) in a hospital patient cohort in Tokyo, Japan, a city with a particularly high SARS-CoV-2 prevalence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation